Implementing assessments via mobile during the acute posttrauma period: feasibility, acceptability and strategies to improve response rates. (3rd December 2018) - Price, Matthew; Van Stolk-Cooke, Katherine; Legrand, Alison C.; Brier, Zoe M. F.; Ward, Hannah L.; Connor, Julie P.; Gratton, Jennifer; Freeman, Kalev; Skalka, Christian
ABSTRACT: Background : PTSD is posited to develop in the acute posttrauma period. Few studies have examined psychopathology symptoms within this period due to the demands on individuals in the first month after a trauma. Mobile devices can overcome these barriers. The feasibility of using mobile devices for this purpose, however, is unclear. Objective : The present study evaluated the acceptability of administering PTSD symptom assessments via a mobile application throughout the acute posttrauma period. Method : Participants ( N  = 90) were recruited from a Level 1 Trauma Center within M  = 4.88 days of experiencing a traumatic event. A mobile application was placed on their smartphone that administered a daily self-report assessment of PTSD symptoms for 30 days. Participants were compensated US$1 for each assessment completed. Results : The overall response rate was 61.1% or M  = 18.33, SD  = 9.12 assessments. Assessments were accessed M =  65.2 minutes after participants were notified to complete them and took M  = 2.52 minutes to complete. Participants reported that the daily assessments were not bothersome and were moderately helpful. Conclusion : The present study suggests that using mobile devices to monitor mental health symptoms during the acute posttrauma period is feasible and acceptable. Strategies are needed to determine how to best take advantage of these data once collected.